Sistem Pendukung Keputusan Penilaian Kinerja Dosen Menggunakan Metode (COPRAS) - Wulandari, Faras Tira; Triayudi, Agung; Mesran, Mesran; Sussolaikah, Kelik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The lecturer performance evaluation decision support system aids the Quality Control Bureau (BPM) in establishing the lecturer performance index (IKD). It employs the Complex Proportional Assessment (COPRAS) method for this assessment. COPRAS facilitates the analysis of diverse alternatives, estimating their utility levels by considering attribute values within intervals, enhancing precision and efficiency in decision-making. The regular evaluation of lecturer performance at the university is pivotal for the continual enhancement of their quality. Thus, a decision support system is imperative to streamline processes and minimize errors in rapidly and accurately computing system data, employing the Complex Proposal Assessment (COPRAS) method. The examination outcomes consistently recognize alternative A4, as the optimal alternative for exemplary lecturer performance, achieving a perfect score of 100.